2022
DOI: 10.18805/ag.d-5492
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vegetable and Fruit Wastes Vermicompost on the Growth and Yield of Black Gram (Vigna mungo L.)

Abstract: Background: Composting is the process of breaking down of organic matter using living organisms which can be used as manure for soil conditioning. Vermicomposting is the rapid decomposition of biowastes using earthworm species which will enhance the growth and yield of plants. Methods: The vermicomposting of vegetable and fruit wastes was carried out during summer season (May-July) and by using the vermicompost a pot culture experiment was conducted in black gram for three months from August to October, 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…This might be due to an increase in the number of branches plant -1 , which may be attributed to robust vegetative expansion, facilitated by the provision of nitrogen through fertilizers and inoculants, which ultimately increase the total branches. These discoveries align harmoniously with the earlier findings of Hussain et al [10], Charles et al [11] and Jat et al [12], as they, reported a substantial increase in the total number of branches with biofertilizer applications.…”
Section: Number Of Branches Plant -1supporting
confidence: 90%
“…This might be due to an increase in the number of branches plant -1 , which may be attributed to robust vegetative expansion, facilitated by the provision of nitrogen through fertilizers and inoculants, which ultimately increase the total branches. These discoveries align harmoniously with the earlier findings of Hussain et al [10], Charles et al [11] and Jat et al [12], as they, reported a substantial increase in the total number of branches with biofertilizer applications.…”
Section: Number Of Branches Plant -1supporting
confidence: 90%
“…Shoot length increased gradually in the treatment 6 (11.8, 25.8 and 30.7 cm) followed by the treatment 3 (11.1, 25.2 and 29.1 cm) compared to the control (8.2, 18.6 and 24.9 cm). Similar results were correlated with Raihing and Vijayalakshmi, (2022) in black gram with the application of vegetable and fruit waste, shoot length was found to be more in treatment-8 (56.9, 62.1 and 71.5 cm) and root length in treatment 8 (14.5,17.2 and 18.5 cm).…”
Section: Discussionsupporting
confidence: 79%